A Theoretical Framework to Measure Social Acceptance of Nuclear Energy among Hungarian Residents - Bihari, Péter (Theory, Methodology, Practice – Review of Business and Management, 2024)
Global warming is a pressing issue, but so does economic development and the constantly increasing electricity demand. Governments have to find the balance between conserving the Earth’s atmosphere for future generations and fueling their country’s economy to achieve higher output. Nuclear energy seems like a solid solution for both problems. It can help to replace the fossil fuels in the electricity mix and at the same time reduce CO2 emission, however thanks to the specificities of the technology a lot of people are skeptical about it. The aim of this study is to review the currently available behavioral and technology acceptance models - such as TRA, TPB, TAM, Risk-Benefit Concept, PADM - and based on the results build a new model, that could serve as a basis for a future survey among Hungarian residents related to the acceptance of nuclear energy generation.